Praktik Sumber Daya Manusia Berkinerja Tinggi: Kepemimpinan Autentik dan Kreativitas Karyawan - Zalindawati .; Adolf Bastian; Ririn Handayani (Jurnal Ekonomika Dan Bisnis (JEBS), 2026)
The study was conducted at the Secretariat of the Regional House of Representatives of Riau Province, aiming to examine the mediating role of HR practices in the relationship between authentic leadership and employee creativity. The research population consisted of 196 employees. Based on this population size, the sample was determined using the population table developed by Krejcie and Morgan (1970), where for N (population) = 196, the required sample size is n = 132. The sampling technique used in this study was simple random sampling. All respondents were involved to obtain primary data related to the variables, which were collected through a questionnaire using a 1–5 point Likert scale. All collected data were analyzed using Structural Equation Modeling (SEM) with Smart PLS 3.0. The study found that authentic leadership has a positive effect on employee creativity; authentic leadership positively influences HR practices; HR practices positively affect employee creativity; and HR practices mediate the influence of authentic leadership on employee creativity.